2020
DOI: 10.1007/s11294-020-09786-0
|View full text |Cite
|
Sign up to set email alerts
|

Exports and Economic Growth: Some Evidence from the GCC

Abstract: A number of studies have identified the positive effect of exports on economic growth (export-led growth (ELG) hypothesis) through enhanced economies of scale, adoption of advanced technology and greater capacity utilization (Feder,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…From another dimension, the humongous export of just one or two primary commodities as is the case in many low income countries could result in the over appreciation of a country"s currency, spurring drastic decrease in the export of other commodities, especially secondary goods; the "Dutch disease" syndrome. An ill performing economy structurally skewed to perpetually underperform could be occasioned by unfavourable trade outcomes or the Dutch disease syndrome; this closely describes the economies of many African countries (Kalaitzi & Chamberlain, 2020).…”
Section: Does Free Trade Make All International Trade Participating Countries Better-off?mentioning
confidence: 99%
See 2 more Smart Citations
“…From another dimension, the humongous export of just one or two primary commodities as is the case in many low income countries could result in the over appreciation of a country"s currency, spurring drastic decrease in the export of other commodities, especially secondary goods; the "Dutch disease" syndrome. An ill performing economy structurally skewed to perpetually underperform could be occasioned by unfavourable trade outcomes or the Dutch disease syndrome; this closely describes the economies of many African countries (Kalaitzi & Chamberlain, 2020).…”
Section: Does Free Trade Make All International Trade Participating Countries Better-off?mentioning
confidence: 99%
“…In that light, countries whose total exports are largely comprised of primary goods are more likely to have their economies exposed to the vagaries of international market and their economic performance inevitably affected by exchange rate and government revenue volatilities that come with it (Kalaitzi & Chamberlain, 2020).…”
Section: Does Free Trade Make All International Trade Participating Countries Better-off?mentioning
confidence: 99%
See 1 more Smart Citation
“…Onifade S T(2020) found that there is a long-term correlation between public expenditure and economic growth, government expenditure has a negative impact on economic growth, and public expenditure and domestic investment are the Granger causes of economic growth [1]; Hasan M A(2019) found that economic globalization and political globalization accelerate economic growth in the long run, but the impact of shortage is not obvious [2]; Haini H(2020) the empirical results show that financial institutions have a significant positive impact on economic growth, but the impact of financial market is not obvious [3]; Kalaitzi A(2020) found that export will increase investment in sectors with comparative advantages, thus increasing economic growth rate. At the same time, export will increase foreign exchange inflow, which will also stimulate economic growth [4]; Gani A(2020) found that China's economic growth has a significant positive impact on Africa, while India's economic impact is not significant [5]; Qamruzzaman, M.(2018) found that financial innovation and economic growth have long-term cointegration. In the long run, financial innovation has a positive impact on economic growth, but the short-term impact is not obvious [6]; Olayungbo D O(2019) found that both long-term and short-term financial development has a positive impact on economic growth [7]; Nguyen H T(2020) found that greenfield investment and cross-border M&A have different effects on economic growth, which is important to the policy of attracting foreign investment [8]; Mohamed Abdouli(2017) found that the inflow of foreign capital can accelerate the economic growth of MENA countries, and the economic growth is easy to cause environmental degradation [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, they found that "export -related growth is associated mainly with capital deepening" which could indicate that exports drive growth by facilitating a country's structural upgrading (Hagemejer andMućk, 2019, p. 1996). Other evidence from small, open economies comes from Greece and the Gulf Cooperation Council countries, where respectively Tsitouras (2016) and Kalaitzi and Chamberlain (2020) found evidence of significant long -run relationships between economic development and export growth.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 99%